P.B. van Voorst van Beest Gallery. - P.B. van Voorst van Beest Gallery, Den Haag (Den Haag : P.B. van Voorst van Beest Gallery, 1984)
Cals, Joseph ; Chagall, Marc ; Collery, Paula ; Delvaux, Paul ; Demuro, Mark ; Elderenbos, Rob ; Hovy, Hans ; Klimt, Gustav ; Kokoschka, Oskar ; Lipski, Donald ; Pascin, Jules ; Renoir, Auguste ; Rodin, Auguste ; Rogge, Cornelis ; Salazar, Jorge ; Schoonhoven, Jan ; Sluijters, Jan ; Visch, Henk ; Vlijm, Marien ; de Vorst, Tony van ; de Vries, Sjoerd ; Zadkine, Ossip
P.B. van Voorst van Beest Gallery, Den Haag, Tony van de Vorst & Sjoerd de Vries, 25 November - 23 december 1984 / Paula Collery, Mark Demuro & Jorge Salazar, September 1 - NOvember 1, 1984 / Joseph Cals, 3 November - 25 November 1984
boek